Transmission of SARS-CoV-2 during indoor clubbing events: A clustered randomized, controlled, multicentre trial protocol - Goupil de Bouillé, Jeanne; Luong Nguyen, Liem Binh; Crépey, Pascal; Garlantezec, Ronan; Doré, Véronique; Dumas, Audrey; Ben Mechlia, Mohamed; Tattevin, Pierre; Gaudart, Jean; Spire, Bruno; Lert, France; Yazdanpanah, Yazdan; et al. (Frontiers in Public Health, 2022)
Introduction: The SARS-CoV-2 pandemic led to the implementation of several non-pharmaceutical interventions (NPI), from closings of bars and restaurants to curfews and lockdowns. Vaccination campaigns started hoping it could efficiently alleviate NPI. The primary objective of the “Indoor Transmission of COVID-19” (ITOC) study is to determine among a fully vaccinated population the relative risk of SARS-CoV-2 transmission during one indoor clubbing event. Secondary objectives are to assess the transmission of other respiratory viruses, risk exposure and attitudes towards COVID-19 vaccination, health pass and psychological impact of indoor club closing. Methods and analysis: 4,400 healthy volunteers aged 18-49 years and fully vaccinated will be included in Paris region. The intervention is an 8-hour indoor clubbing event with no mask wearing, no social distancing, at maximum room capacity, with ventilation. Participants will be recruited by group of up to 10, to be randomized 1:1 to experimental group (2,200 volunteers in two venues with a capacity of 1000 persons each) or control group (2,200 volunteers asked not to go to club). All participants will provide a salivary sample the day of experiment and seven days later. They also will answer several questionnaires. Virological analyses include polymerase chain reaction (PCR) of salivary samples and air of the venue, investigating SARS-CoV-2 and 18 respiratory viruses. Ethics and dissemination: Ethical clearance was first obtained in France from the institutional review board (Comité de Protection des Personnes Ile de France VII - CPP), and the trial received clearance by the French National Agency for Medicines and Health Products (Agence National de Sécurité du Médicament - ANSM). The trial is supported and approved by The Agence Nationale Recherche sur le SIDA, les hépatites et maladies émergences (ANRS-MIE). Positive, negative and any inconclusive results will be published in peer-reviewed scientific journals. Trial registration number: Eudra-CT 2021-A01473-38. Clinicaltrial.gouv ID : NCT05311865